Catalyst- and Additive-Free Synthesis of Fluoroalkoxyquinolines - Dhiman, Ankit Kumar; Kumar, Rohit; Sharma, Upendra (Synthesis, 2021)
A nucleophilic substitution approach has been developed for the synthesis of C4 fluoroalkoxyquinolines from 4-haloquinolines by utilizing hexafluoro-2-propanol and trifluoroethanol as nucleophiles. The method is also applicable for 2-chloroquinolines, 1-chloroisoquinoline, and 2-chlorobenzimidazole. Control experiments revealed that substitution occurs only at the C2 and C4 positions of quinolines.
Keywords: 4-chloroquinoline; 2-chloroquinoline; 1-chloroisoquinoline; HFIP; fluoroalkoxylation